VE-Cadherin Is Required for Cardiac Lymphatic Maintenance and Signaling. Issue 1 (18th November 2021) - Harris, Natalie R.; Nielsen, Natalie R.; Pawlak, John B.; Aghajanian, Amir; Rangarajan, Krsna; Serafin, D. Stephen; Farber, Gregory; Dy, Danielle M.; Nelson-Maney, Nathan P.; Xu, Wenjing; Ratra, Disha; Hurr, Sophia H.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The adherens protein VE-cadherin (vascular endothelial cadherin) has diverse roles in organ-specific lymphatic vessels. However, its physiological role in cardiac lymphatics and its interaction with lymphangiogenic factors has not been fully explored. We sought to determine the spatiotemporal functions of VE-cadherin in cardiac lymphatics and mechanistically elucidate how VE-cadherin loss influences prolymphangiogenic signaling pathways, such as adrenomedullin and VEGF (vascular endothelial growth factor)-C/VEGFR3 (vascular endothelial growth factor receptor 3) signaling. Methods: Cdh5 flox/flox ;Prox1CreER T2 mice were used to delete VE-cadherin in lymphatic endothelial cells across life stages, including embryonic, postnatal, and adult. Lymphatic architecture and function was characterized using immunostaining and functional lymphangiography. To evaluate the impact of temporal and functional regression of cardiac lymphatics in Cdh5 flox/flox ;Prox1CreER T2 mice, left anterior descending artery ligation was performed and cardiac function and repair after myocardial infarction was evaluated by echocardiography and histology. Cellular effects of VE-cadherin deletion on lymphatic signaling pathways were assessed by knockdown of VE-cadherin in cultured lymphatic endothelial cells. Results: Embryonic deletion of VE-cadherin produced edematous embryos with dilated cardiac lymphatics with significantly altered vessel tip morphology. Postnatal deletion of VE-cadherin caused complete disassembly of cardiac lymphatics. Adult deletion caused a temporal regression of the quiescent epicardial lymphatic network which correlated with significant dermal and cardiac lymphatic dysfunction, as measured by fluorescent and quantum dot lymphangiography, respectively. Surprisingly, despite regression of cardiac lymphatics, Cdh5 flox/flox ;Prox1CreER T2 mice exhibited preserved cardiac function, both at baseline and following myocardial infarction, compared with control mice. Mechanistically, loss of VE-cadherin leads to aberrant cellular internalization of VEGFR3, precluding the ability of VEGFR3 to be either canonically activated by VEGF-C or noncanonically transactivated by adrenomedullin signaling, impairing downstream processes such as cellular proliferation. Conclusions: VE-cadherin is an essential scaffolding protein to maintain prolymphangiogenic signaling nodes at the plasma membrane, which are required for the development and adult maintenance of cardiac lymphatics, but not for cardiac function basally or after injury.